Evaluation of Surface Characteristic Changes of WaveOne Gold and WaveOne Single Reciprocating Files Using Scanning Electron Microscopy: An in-vitro Study - Ahmed Menecy; Nayera Mokhless; Seham Hanafy (Mashhad University of Medical Sciences, 2018)
Introduction: The purpose of this study was to evaluate surface topography of WaveOne Gold (WOG) and WaveOne (WO) ﬁles using SEM before and after use. Methods: Twelve primary files from each system were scanned for surface defects before instrumentation at 100x and 750x. Each file was planned ti be used to instrument six root canals and then examined under SEM after preparing one, three and six canals at same magnifications. Data were scored and statistically analyzed using Mann Whitney and Friedman tests  (p≤ 0.05). Results: Surface defects were detected in both study groups with higher values in WOG group before use. Surface defects significantly increased in both WO and WOG groups after use. WOG group showed significantly greater defects including metal strips, pitting, craters, micro-cracks and blunt edges (p≤ 0.05). Conclusion: WaveOne Gold file has a different metallurgy due to it's gold finish that does not enhance it's resistance to surface defects during clinical use.